ENT 530 Case Study: Medina Yasmin / Muhamad Rafiqin Razali ... [et al.] - Razali, Muhamad Rafiqin; Mohd Naseri, Natasha Amira; Hamdan, Murni Amiera; Ahmad Zaidi, Puteri Nik Nursyafika; Tuan Mukhtar, Tuan Aimin Syahmie; Zaidi, Nur Khaleeda; Pg Zaidi, Dk Siti Nursyuhada; Anuar, Alia Yasmin; Ungku Zanedreef Shah, Ungku Zanedameral Haleq (2021)
This slide is about pointing out the process, issues, and ventures of an entrepreneur who experienced life of a business which is done by finding an existing business and perform an interview regarding the entrepreneurship journey. From it, detailed company information are displayed within, including SWOT analysis that are done on the business. Discussions and solutions on how to improve the business and resolve issues are prepared to simulate the steps required for the business to grow and sustain. This will help beginners to learn on how to be an entrepreneurs based on the experiences of an existing ones.